Analysis of the Role of the Waqf Nazir in the Management of the Mosque in Review of the Minister of Religious Affairs Regulation Number 54 of 2006 - Habib, Muhammad Khairi; Harahap, Abd. Rahman (Jurnal Daulat Hukum, 2024)
As-Syukriyah Mosque in Tanjungbalai City is one of the new mosques whose management has deviated from the relevant legal provisions. Based on Law Number 41 of 2004, the Waqf Nazir does not have the duties and authority of the Mosque Prosperity Board (BKM). However, in As-Syukriyah Mosque, the Waqf Nazir actually plays a full role in carrying out the duties and authority of the BKM. This situation is caused by the absence of an official certificate from the local Religious Affairs Office (KUA) that establishes the mosque's BKM management structure. This research uses a normative juridical approach to analyze the legal norms governing the duties of the Waqf Nazir as well as the role of the KUA in the establishment of BKM in accordance with the Minister of Religious Affairs Regulation No. 54 of 2006. The results show that the mosque is still managed independently by the Waqf Nazir without community involvement and without an official decree from the KUA, although according to existing regulations, As-Syukriyah Mosque is categorized as a District/City BKM. This condition shows the need to improve mosque governance in accordance with applicable laws and regulations.